Pengaruh Budaya Organisasi dan Iklim Organisasi terhadap Komitmen Pegawai : Studi pada Pegawai Negeri Sipil di 4 Kecamatan Kabupaten Sumba Tengah - Ardianto Umbu Sunga; Adya Hermawati; Dharmayanti Pri Handini (Transformasi: Journal of Economics and Business Management, 2024)
The aim of this research is to analyze the influence of organizational culture and organizational commitment on employee commitment. This research is quantitative research with a descriptive approach using primary and secondary data types. The data collection techniques used were interviews, documentation and field observations. The data collected was in the form of distributing questionnaires to 30 respondents and will be analyzed using multiple linear regression models, classical assumptions and hypothesis testing.The results of data analysis in this research show that partially organizational culture and organizational climate have a significant and positive effect on employee commitment, while simultaneously also showing that organizational culture and organizational climate have a significant effect on employee commitment.